Evaluación de la viabilidad de células vero empleando extractos de los hongos shiitake y maitake como sustituto del suero fetal bovino (2017)
"Currently a fetal bovine serum (FBS) replacement is trying to be developed from a non animal origin. This project seeks to assess the efficiency of shiitake and maitake mushroom extracts as FBS replacements in Vero cell cultures because their nutritional components and literature suggest they can replace FBS in cell cultures. An extract of each mushroom, was obtained by blending with PBS and subsequent 0.2 ?m filter filtration. The toxicity of each of the extracts was evaluated separately (6 replicates) and in combination (4 replicates). This was followed by an experiment to accustom the cells to the media with each of the extracts separately in which the SFB content was lowered and replaced by the extracts over 4 passes and the morfological changes of the cells were observed. The toxicity results showed that the fungal extracts did present toxic components as the cell viability decreased compared to the controls. Pearson's correlation coefficient indicated that the maitake extract exhibited a toxicity proportional to the amount of extract in the medium in 4 of 6 experiments, whereas for the shiitake extract the same behavior was observed in only 1 of 6 experiments." -- Tomado del Formato de Documento de Grado.